NATIONALITY AND THE ART OF IMAGES IN THE WORKS OF KAMCHIBEK KENJA (International conference on multidisciplinary science, 2025)
The article examines the art of nationality and imagery in the novel “Pledge” by the writer Kamchibek Kenja. The essence of the plot, the skill of the writer, and the chronotope of the work are discussed.